The Effects of A Group Counseling Program Based on The Cognitive-Behavioral Approach on The Self-Esteem of Students At The Non-Formal And Informal Education Center in Yala Province. - Charoensuk, Siriluck; Dudsdeemaytha, Jitra (Saengtham College Journal, 2024)
The objective of this research is to study the effects of a group counseling program based on the cognitive-behavioral approach on the self-esteem of students at the non-formal and informal education center in Yala Province, and with a quasi-experimental design. The sample group consisted of students from non-formal and informal education centers with low self-esteem scores (average score 1.00-2.00), a total of 36 individuals. They were divided by using simple randomization via drawing lots to assign into experimental and control groups, with 18 subjects in each group. The research instruments were the self-esteem assessment questionnaire, and a group counseling program based on cognitive-behavior approach, was conducted eight times. The data were analyzed using mean, standard deviation, and a t-test. The major findings were as follows: (1) after the experiment, students in the experimental group who participated in the group counseling program based on the cognitive-behavioral approach had significantly higher self-esteem scores than before joining the program, at a statistically significant level of .01; and (2) after the experiment, these students in the experimental group who participated in the group counseling program based on the cognitive-behavioral approach had higher self-esteem scores compared to the control group, and with a statistical significance of .01.